2007
DOI: 10.1183/09031936.00032407
|View full text |Cite
|
Sign up to set email alerts
|

Experience with inhaled iloprost and bosentan in portopulmonary hypertension

Abstract: Novel treatments, such as prostanoids or endothelin receptor antagonists, have been introduced for various forms of pulmonary arterial hypertension, but the long-term effects of these treatments on portopulmonary hypertension (PPHT) are unknown.In a retrospective analysis, the present authors assessed the safety and efficacy of inhaled iloprost, a prostacyclin analogue, and bosentan, an endothelin receptor antagonist, in patients with PPHT. In total, 31 consecutive patients with Child class A or B cirrhosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
1
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 32 publications
1
115
1
10
Order By: Relevance
“…Case series suggest that epoprostenol, bosentan and sildenafil may exert beneficial haemodynamic and clinical effects in selected patients [208][209][210]. In a retrospective study treatment with bosentan appeared to be better than inhaled iloprost [211]. Careful monitoring should be performed if ERA treatment is initiated because of the hepatotoxicity of these compounds.…”
Section: Therapymentioning
confidence: 99%
“…Case series suggest that epoprostenol, bosentan and sildenafil may exert beneficial haemodynamic and clinical effects in selected patients [208][209][210]. In a retrospective study treatment with bosentan appeared to be better than inhaled iloprost [211]. Careful monitoring should be performed if ERA treatment is initiated because of the hepatotoxicity of these compounds.…”
Section: Therapymentioning
confidence: 99%
“…Inhibitors of 1-endothelin as bosentan are an effective treatment in stable hepatic illness, however there is insufficient evidence of its effectiveness in patients with altered hepatic dysfunction [16]. Furthermore, patients treated with bosentan have shown better results in hemodynamic parameters and the 6 minute-walk distance test (6MWD) compared with patients treated with inhaled iloprost [17]. It has been demonstrated that treatment with ambrisentan has less hepatic toxicity and improves hemodynamic parameters with respect to bonsentan [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, in one study, the treatment was stopped in half of the patients because of the following adverse effects: chin pain, diarrhea, erythema, arthralgia, infections, sepsis due to a catheter, thrombus, pump dysfunction, hypersplenism, impairment of liver function, and rebound pulmonary hypertension (7). Due to its excessive adverse effects and the difficulty with intravenous administration, inhaled iloprost has been the preferred treatment (6). Inhaled iloprost provides an enhancement in functional capacity; however, this improvement is not maintained in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of mortality is close to 0% if the mean PAP is lower than 35 mmHg (5). However, the risk of mortality rises to 50% if the mean PAP is between 35-45 mmHg, and it increases to nearly 100% when the mean PAP is greater than 45 mmHg (3,6). If the preoperative pressure is reduced to levels below 35 mmHg, transplantation may be performed confidently.…”
Section: Discussionmentioning
confidence: 99%